"Skin rashes" and immunotherapy in melanoma: distinct dermatologic adverse events and implications for therapeutic management. Issue 3 (31st May 2022) - Sollena, Pietro; Cappilli, Simone; Federico, Francesco; Schinzari, Giovanni; Tortora, Giampaolo; Peris, Ketty
ABSTRACT: Immune checkpoint inhibitors have shown efficacy in the treatment of different cancers by stimulating the antitumoral activity of the patient's immune system, representing a major breakthrough in the field of cancer therapy. Monoclonal antibodies including anti-cytotoxic T-lymphocyte–associated protein 4, anti–programmed cell death protein 1 and its ligand inhibitors have been approved for advanced melanoma among other solid cancers. Although immunotherapy demonstrated a good safety profile, a new spectrum of multisystemic immune-related adverse events has been recently reported due to their use. Cutaneous reactions represent one of the leading adverse events, often reported in literature as "skin rash", and rarely further characterized in distinct dermatologic entities. Herein we describe the distinctive cutaneous rashes occurring during immunotherapies for advanced melanoma, discussing implications in the treatment management.